In Vitro Comparison of Pediatric Oxygenators With and Without Integrated Arterial Filters in Maintaining Optimal Hemodynamic Stability and Managing Gaseous Microemboli. Issue 4 (26th January 2018) - Moroi, Morgan; Force, Madison; Wang, Shigang; Kunselman, Allen R.; Ündar, Akif
Abstract: The purpose of this study was to compare the Capiox FX15 oxygenator with integrated arterial filter to the Capiox RX15 oxygenator with separate Capiox AF125 arterial filter in terms of hemodynamic properties and gaseous microemboli (GME) capturing. Trials were conducted at varying flow rates (2.0 L/min, 3.0 L/min, 4.0 L/min), temperatures (30°C, 35°C), and flow modalities (pulsatile, nonpulsatile). Pressure and flow waveforms were recorded using a custom‐made data acquisition system. GME data were recorded using an Emboli Detection and Classification Quantifier after injecting a 5 mL air bolus into the venous line. Maximum instantaneous pre‐oxygenator flows reached 7.4 L/min under pulsatile conditions when the roller pump was set to a flow rate of 4 L/min. Mean pressure drops were slightly greater in the FX15 group ( P  < 0.0001), and the diverted flow from the arterial purge line was slighter greater in the FX15 group at 3 L/min and 4 L/min ( P  < 0.0001). There was a slight generation of surplus hemodynamic energy (SHE) at the pre‐oxygenator site for both oxygenators under "nonpulsatile mode." However, higher pre‐oxygenator SHE levels were recorded for both groups with "pulsatile mode." The RX15 and FX15 groups were both able to remove all microemboli from the circuit at 2 L/min and 3 L/min in "nonpulsatile mode." Microemboli were delivered to the patient at 4 L/min with pulsatile flows in both groups. The RX15 oxygenator with separate AF125 arterial filter and FX15 oxygenator with integrated arterial filter performed similarly in terms of hemodynamic performance and microemboli capturing. Pulsatile flows at 4 L/min produced instantaneous flow rates that surpassed the documented maximum flow rates of the oxygenators and might have contributed to the delivery of GME to the pseudo‐patient.